The effect of electro-thermal treatment of stainless steel arch wire on mechanical properties and cell proliferation - Gu Yingzhi; Xie Xianju; Wang Hongmei; Zhuang Rui; Bai Yuxing (Sciendo, 2020)
Electric resistance heat treatment may be performed on orthodontic arch wires, but it remains unclear whether this procedure reliably provides better mechanical properties or whether an austenite phase transition affords less cytotoxicity and less arch wire width change.